The Analysis Study of Comparison Clinical Scoring System in Pulmonary Embolism: A Comprehensive Systematic Review - Meirisa; Stevany Nurifin; Mely Christina Damanik (The International Journal of Medical Science and Health Research, 2025)
Background: Pulmonary embolism is a significant diagnostic challenge in emergency departments due to its life-threatening nature and non-specific symptoms. Diagnostic systems like CTPA have been developed to address these challenges, but their limitations and radiation exposure raise concerns about patient safety. Comparing clinical scoring systems for pulmonary embolism can enhance diagnosis yield and optimize resource allocation. Methods: This systematic review adhered to PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2014 and 2024. Editorials and review articles without a DOI were excluded to ensure the utilization of high-quality sources. A literature review was conducted utilizing reputable databases including ScienceDirect, PubMed, and SagePub to identify relevant studies. Result: The initial database search identified nearly 200 publications pertinent to the topic. After a thorough three-stage screening process, eight studies were chosen that satisfied the established inclusion criteria for detailed analysis. The studies underwent a thorough critical evaluation, facilitating a detailed examination of the comparison clinical scoring system in pulmonary embolism. This targeted methodology guaranteed that the analysis utilized robust evidence closely aligned with the study's aims. Conclusion: Pulmonary embolism diagnosis accuracy has been significantly improved by integrating clinical scoring systems with D-Dimer testing and PERC. Combinations like WS + PERC and RGS + PERC achieved near-perfect sensitivity, reducing failure rates. However, trade-offs exist between sensitivity and specificity, necessitating further research.